Ed Emberley's complete funprint drawing book. - Emberley, Ed. (New York : Little, Brown, 2002)
Instructions for creating a variety of shapes and figures using thumbprints or fingerprints and a few simple lines.
Two books in one: Fingerprint drawing book & Great thumbprint drawing book -- cover.
1-2
Keywords: Drawing -- Technique -- Juvenile literature; Thumbprints in art -- Juvenile literature; Fingerprints in art -- Juvenile literature